The project management tool kit : 100 tips and techniques for getting the job done right - Kendrick, Tom (AMACOM/American Management Association, 2004)
The Project Management Tool Kit presents proven project management practices in an accessible, easy-to-apply format Based on established methodologies used by successful project managers in many fields, the Tool Kit features comprehensive summaries of all the processes outlined in the most recent edition of the PMBOK® (Project Management Body of Knowledge). Complete with checklists and other tools for quick implementation, here is a practical and complete guide to mastering any project challenge.